Performance and impact of clinical genome sequencing in patients with suspected rare genetic diseases in Peru - Thorpe, Erin (2024)
Molecular genetic testing has limited access in many regions across the world, especially in developing countries. The iHope program philanthropically provides clinical genome sequencing (cGS) to individuals with signs or symptoms of rare genetic diseases and limited or no access to molecular genetic testing.